2007
DOI: 10.3390/ijerph2007040006
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Cytotoxicity and Genotoxicity of a Sunscreen Agent, 2-Phenylbenzimidazole in Salmonella typhimurium TA 102 and HaCaT Keratinocytes

Abstract: 2-Phenylbenzimidazole (PBI) is an ingredient found in sunscreen agents. PBI can absorb the UV portion of the solar light and undergo a series of light-induced reactions to cause adverse effects in humans. Therefore, chemical and photochemical toxicity of PBI were investigated in the bacteria Salmonella typhimurium TA 102 and human skin keratinocyte cells. There is no appreciable bacteria death due to the exposure to PBI alone, indicating that PBI is not chemically toxic to the bacteria at a dose as high as 625… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Indirect DNA damage has raised concerns that some of the chemicals in certain sunscreens could contribute to free radical production and hence cellular damage. [27][28][29] An example reaction is illustrated in Fig. 3.…”
Section: A2 Indirect Dna Damagementioning
confidence: 99%
“…Indirect DNA damage has raised concerns that some of the chemicals in certain sunscreens could contribute to free radical production and hence cellular damage. [27][28][29] An example reaction is illustrated in Fig. 3.…”
Section: A2 Indirect Dna Damagementioning
confidence: 99%
“…The CPDs are the major contributors to mutations in mammals, as they are repaired less quickly than (6-4) photoproducts. Recent studies suggest that some of the existing UVfiltering agents can form harmful photodegradation products (Hanson et al, 2006;Mosley et al, 2007;Burnett and Wang, 2011). Therefore, there is a pressing need for new strategies of photoprotection to reduce the detrimental effects of UVR.…”
mentioning
confidence: 99%
“…There are studies on the cytotoxic 21,22 and genotoxic effects 21,23,24 of organic UV filters on different cell lines. It was reported that UV filters caused mitochondrial stress and inhibited cell growth in different cultured human cells.…”
Section: Discussionmentioning
confidence: 99%